Competencies and skills of the accounting professional: what do administration and accounting students think? (Research, Society and Development, 2021)
This research aimed to analyze the perception of administration and accounting students about competencies and skills of the accounting professional. Therefore, questionnaires were applied to 237 students from a public university in the State of Ceará. The data collection instrument was adapted from the study by Reis, Sedivama, Moreira and Moreira (2015). Data were analyzed using words evocation method, descriptive analysis and Mann-Whitney test. The results, based on the words evocation, suggest that the administration students pointed out more characteristics related to "intellectual and knowledge skills", while the accounting students evoked more words related to "personal skills and competencies". The set of competencies least mentioned by students in both courses was in relation to “organizational skills and competencies and interpersonal relationships”. The Mann-Whitney test showed statistical differences between the groups of respondents, highlighting the differences between the perceptions of students from different courses, suggesting that, in fact, administration and accounting students have different perceptions regarding competencies and skills of the accounting professional.